Low temperature storage of mangoes (Mangifira Indica var. Carabao) in perforated polyethylene bags - Banzon, Cecilia Fernandez; De Leon, Sonia Y. (1969)
Mature green mangoes packed in polyethylene bags with varying perforations were kept at 48 ± 6 °F over a four-week period. Storage life after four weeks was the same for all treatments including unpackaged refrigerated mangoes. High CO2 and low O2 content of non-perforated bags delayed ripening time after storage and resulted in off-odors and flavors after three weeks of storage. Slight chilling injury was manifested through lack of flavor. Unpackaged mangoes were more acceptable than all prepacked mangoes after three weeks of storage although they were considerably shriveled. Response to prepackaged mangoes were favorable up to two weeks storage at 48 °
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mango; Mango -- Storage